Development of Auto Car Jack Using Internal Car Power - M. M., Noor; K., Kadirgama; M. M., Rahman; M. R. M., Rejab; M. S. M., Sani (2008)
Car jacks usually use mechanical advantage to allow a human to lift a vehicle by manual force. More powerful jacks are using hydraulic power to provide more lift over greater distances. This paper presents the development of the car jack for emergency use with using internal cigarette lighter power (12volts). The automatic easy car-jack utilizes this power source to save individuals having to exert any energy. To increase the lifting power in order to ensure the power is adequate, gear ratio was used. The car jacker was developed utilizing the Solidworks® and its analyses to check the safety factor and force acting. The fabrication work has been done with milling and grinding machine. The car jacker will be tested and it predicted to have enough power to lift and holding the car as normal car jacker.